Pemikiran Mahmud Muhammad Thaha tentang Syariat yang Humanis - Azwarfajri Azwarfajri (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Mahmud Muhammad Thaha, a Sudanist Islamic thinker, tries to issue a new Islamic perspective on Islamic law. According to him, Islam has two main periods; Mecca period (610-622M.) and Medina period (623-632M). The former, called al-risalah al-ula and the latter, called al-risalah al-thaniyah. The nuances of al-risalah al-ula it is universal, substantive, protective the all mankind, equal and democratic. Whereas al-risalah al-thaniyah it becomes “established Islam” and protected the internal ummah with locally and temporarily additional rules. Some additional rules are not derived from the original sources of Islam, the Qur’an and hadith. Therefore, according to Thaha, Islamic law needs to be reformed in order to adjust it to the demands of modern time so that Islamic law play sicnificant role in the formation of humanist and democratic world.